A biotecnologia como instrumento de desenvolvimento social e ambiental aplicado a palma forrageira - Dutra, Maria de Fátima Batista (2021)
In the semiarid region of the Northeast of Brazil, rainfall fluctuations have negatively influenced the achievement of satisfactory results of small farmers’ methodologies of exploitation, creating severe consequences on their income and therefore on their lives. The people from the Northeast have not yet found the synchronism between the traditional culture and the imperatives of the environment. A relevant fact to this region is that the cacti in the semiarid environment are extremely important for the sustainability of the caatinga biome, which work as a source of fodder and food for animals, especially in periods of prolonged drought, with emphasis on the cactus pear. One of the greatest difficulties for the development of the cactus pear cultivation is the limited availability of cultivation material, for the conventional propagation system is very slow. Thus, biotechnology becomes a tool of great importance to provide benefits to different sectors of society, especially agriculture. For this reason, micropropagation has been used successfully in several species, aiming at an efficient multiplication system for these cacti. In view of this, the general objective of this research was to investigate through biotechnology a method of fast and efficient propagation for the cactus pear tolerant to carmine cochineal to be used in the northeastern semiarid, contributing to the improvement of the agricultural and economic potential in Rio Grande do Norte and consequently to the living with the semiarid region. In doing so, this research sought to develop micropropagation protocols with two varieties of cactus pear, Elephant Ear and Miúda, compared the pattern of in vitro development and carried out greenhouse acclimatization tests, pointing out materials tolerant to carmine cochineal and conducive to be cultivated in this region. In the last chapter, through the application of questionnaires to family farmers, the socioeconomic profile of those who cultivate cactus pear of the varieties studied was identified in some counties of Rio Grande do Norte. In short, after 120 days of in vitro cultivation it was found that the methodology applied has the potential to increase the yield in the multiplication of high-value genetic materials for the culture of cactus pear, and the two varieties studied are promising and have shown an excellent adaptation in the acclimatization phase. The farmers’ socioeconomic profile was characterized by the presence of some relevant particularities in the counties of Rio Grande do Norte, such as male predominance, subsistence farming, low level of education, plantation in conventional cultivation system and the absence of pest control. The information on the cultivation of cactus pear reported in this research demonstrates its potential, however there are still many elucidations about its usefulness and applications that must be investigated.